Fatal motor vehicle crashes on road segments in Harbin, China: combining rates into contributory factors - Wang, Yonggang; Zhang, Chunbo; Mao, Chengyuan (Transport, 2013)
In spite of recent advances in traffic surveillance technology and ever-growing concerns over the safety performance improvement, there have been very few conclusive research efforts addressing the segment-involved traffic crashes. This research aims at evaluating the segment-involved crashes using 10 years of documented crash data (2000–2010) in Harbin. The interactions of crash patterns, distribution features, injury severity and potential causes are explored by mining a variety of contributory factors associated with driver demographics, roadway geometric design, environmental state, distribution of traffic flow, etc. Results show that different crash patterns are correlated with a number of risk factors at different roadway locations such as the driver’s age and experience, weather, with or without median/division, number of lane, deviation of travelling speed, Annual Average Daily Traffic (AADT), volume to capacity ratio (v/c), and so on, and different combinations of factors may lead to some specific crash patterns such as head-on, angle or rear-end collisions. Moreover, four black locations with a huge number of crashes are identified due to heavy truck involvement on these in/out roads. These findings will help to better understand what, when and why these crashes occur and develop more targeted and cost-effective countermeasures to enhance the overall safety performance of the roadway network. First Published Online: 16 Jul 2013